NOTA CIENTÃFICA: SINTOMATOLOGIA DO ATAQUE DE Calacarus heveae EM SERINGUEIRA (Hevea brasiliensis) - Vieira, Marineide R.; Fabri, Eliane G.; Oliveira, Emerson A. (REVISTA DE AGRICULTURA, 2015)
NOTA CIENTÃFICA: SINTOMATOLOGIA DO ATAQUE DE Calacarus heveae EM SERINGUEIRA (Hevea brasiliensis)